Morphological analysis of Cu substituted Ni\Zn in Ni-Zn ferrites - Parajuli, D.; Samatha, K. (BIBECHANA, 2021)
Cu substituted Ni in Ni0.5-xCuxZn0.5Fe2O4 (x = 0, 0.05, 0.1, 0.15 and 0.2) samples and Cu substituted Zn in Ni0.5Zn0.5−xCuxFe2O4 (x = 0, 0.05, 0.1, 0.15 and 0.2) is synthesized using the sol-gel auto-combustion process. Recently, we have carried out their structural analysis using XRD and FTIR and found a cubic spinel structure. In this paper, we have studied their morphological and compositional structure with the help of a Scanning Electron Microscope (SEM) attached with an Energy Dispersive Spectrometer (EDS). The comparative study shows that the grain size of Cu substituted Ni is greater than Cu substituted Zn in Ni-Zn ferrite. These smaller grain-sized ferrites are preferred for many microstructural applications. Depending on the available magnetic field, sintering temperature, and atmosphere, they can have different nucleation, and hence their application mode is different. They can have a critical concentration that can tune their properties. The EDS attached with the SEM confirmed the proper composition of samples. BIBECHANA 18 (2) (2020) 80-86